Design and Implementation of an ESP32-Based Smart Home Electricity Monitoring and Control Module Using MQTT Dash and Telegram Integration - Muh Asnoer Laagu; Bayu Retno Joyo Nendriyo; Iftiqori Fiqi Anshori; Immawan Wicaksono; Ali Rizal Chaidir (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
This study presents the design and implementation of an ESP32-based smart home box module that integrates multi-channel load control, real-time electrical energy monitoring, and automated user reporting within a single compact and modular system. The proposed module employs an eight-channel relay for household appliance control using the MQTT communication protocol, with MQTT Dash providing real-time visualization and manual control. Electrical parameters, including voltage, current, active power, and cumulative energy consumption (kWh), are measured using a PZEM-004T sensor and transmitted continuously via MQTT. The main contribution of this work lies in the unified system architecture that consolidates device control, energy measurement, and user interaction without reliance on proprietary cloud platforms. In addition to dashboard-based monitoring, a Telegram bot is integrated to deliver real-time system status notifications, on-demand energy reports summarizing average power and total consumption, and fully automated 24-hour periodic reports. This dual interaction mechanism enables both active real-time supervision and passive long-term monitoring, addressing limitations commonly found in prior IoT smart home implementations. Experimental evaluations confirm that the proposed system operates reliably, responsively, and with acceptable measurement accuracy for residential applications. All relays on the eight-channel module respond stably to ON/OFF commands from the MQTT Dash interface with delays of less than one second, ensuring dependable real-time control. The PZEM-004T-based monitoring subsystem provides voltage, current, power, and energy data with power measurement errors ranging from 0.83% to 2.66%, which is suitable for daily household energy monitoring. Tests under various single and combined load conditions demonstrate consistent detection of power variations. Overall, the results indicate that the proposed smart home box module provides a practical, low-cost, and scalable solution for integrated IoT-based residential energy control and monitoring.